KEDUDUKAN AHLI WARIS YANG PENERIMA HIBAH DARI ORANG TUA TERHADAP AHLI WARIS LAINNYA PADA PROSES PEMBAGIAN WARIS - Sanjaya, Umar Haris; Suprapton, Muhammad Yusuf (Jurnal Yuridis, 2017)
This research focused on the clarification in the meaning of legal status of the heir which is the heir received the donation (grant) from the parents before. In fact, the other heirs does not recognize the position of donation receiver to gets inheritance rights belong to parents. This research using context of probles as how the legal status of the heir (donation receiver) belong to the other heirs in receiving inheritance, is the donation receiver does not has rights in inheritance. Research result found that meaning of donation in the 3 perspective of private law giving the  similar consequences, thus are based on private law (civil code), adat law, and islamic fiqih law (KHI). Those are giving perspective that donation is recognized as the inhertance. And the legal status of receiver donation is available to receive inheritance.